The effect of polar auxin transport on adventitious branches formation in Gracilaria lichenoides in vitro. Issue 3 (8th June 2016) - Wang, Wenlei; Li, Huanqin; Lin, Xiangzhi; Zhang, Fang; Fang, Baishan; Wang, Zhaokai
Abstract : Seaweed tissue culture (STC) is an important micropropagation tool that has been applied for strain improvement, micropropagation and genetic engineering. Because the mechanisms associated with STC are poorly understood, its application to these organisms lags far behind that of tissue culture propagation of higher plants. Auxin, calcium (Ca 2+ ) and hydrogen peroxide (H2 O2 ) fluxes all play key roles during plant growth and development. In this study, we therefore measured indole‐3‐acetic acid, Ca 2+ and H2 O2 fluxes of Gracilaria lichenoides explants during adventitious branches (ABs) formation for the first time using noninvasive micro‐test technology. We confirmed that polar auxin transport (PAT) also occurs in the marine red alga G. lichenoides . We additionally found that N‐1‐naphthylphthalamic acid may suppress auxin efflux via ABCB1 transporters and then inhibit ABs formation from the apical region of G. lichenoides segments. The involvement of Ca 2+ and H2 O2 fluxes in PAT‐mediated AB formation in G. lichenoides was also investigated. We propose that complex feedback among Ca 2+, H2 O2 and auxin signaling and response systems may occur during ABs polar formation in G. lichenoides explants, similar to that in higher plants. Our results provide innovative insights that should aid future elucidation of mechanisms operative during STC.